A comparison between cisatracurium and rocuronium-induced neuromuscular block on laryngeal electromyography recovery after neostigmine reversal in a porcine model - Lu, I-Cheng; Tan, Hao; Wu, Sheng-Hua; Huang, Tzu-Yen; Tseng, Hsin-Yi; Wang, Jia-Joanna; Dionigi, Gianlorenzo; Chai, Young Jun; Chiang, Feng-Yu; Chang, Pi-Ying; Wu, Che-Wei (Frontiers in Endocrinology, 2022)
Background: Inducing and reversing neuromuscular block is essential to a positive outcome of thyroid surgery, with intraoperative neuromonitoring (IONM) being used to decrease recurrent and superior laryngeal nerve injuries and improve vocal outcome. Neostigmine is a non-specific broad-spectrum and inexpensive reversal agent for neuromuscular blocking agents (NMBAs). The aim of this porcine study was to explore the effect of neostigmine on electromyography (EMG) signal recovery profile following the commonly used NMBAs, cisatracurium and rocuronium. Methods: Twelve piglets were allocated into two groups with six piglets in each group. When stable baseline EMG signals were obtained, a neuromuscular block was induced by intravenous cisatracurium 0.2 mg/kg (group C) or rocuronium 0.6 mg/kg (group R) for each piglet. We compared laryngeal EMG tracing with spontaneous recovery (control) and neostigmine (0.04 mg/kg) reversal for each group. The time course of real-time laryngeal EMG signals was observed for 30 min from NMBA injection. Effects of neostigmine on EMG signal were assessed at 50% EMG recovery and by the maximum neuromuscular block recovery degree from the baseline value. Results: Neostigmine shortened the recovery time to 50% EMG amplitude in both group C (16.5 [2.5] vs. 29.0 [2.0] min, P<0.01) and group R (16.5[2.5] vs. 26.5 [1.5] min, P<0.05) compared to spontaneous recovery, respectively. Neostigmine reversal also enhanced the maximum degree of EMG amplitude recovery in both group C (83.6 [5.1] vs. 47.2 [6.1] %, P<0.01) and group R (85.6 [18.2]vs. 57.1 [6.3] %, P<0.05) compared to spontaneous recovery, respectively. The reversal effect of neostigmine did not differ significantly between cisatracurium and rocuronium. Conclusions: This porcine model demonstrated that neostigmine provides an adequate and timely IONM signal, suppressed by both cisatracurium and rocuronium. These results can potentially expand the options for precision neuromuscular block management during IONM to improve vocal outcomes in thyroid surgery patients.